2020
DOI: 10.4314/sajas.v50i4.13
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of non-genetic and genetic influences underlying the growth of Kajli lambs

Abstract: Data on 2931 Kajli lambs, born from 2007 to 2018, were used to quantify environmental and genetic effects on growth performance of Kajli sheep. Traits considered for evaluation were birth weight (BWT), 120-day adjusted weight (120DWT), 180-day adjusted weight (180DWT), 270-day adjusted weight (270DWT), and 365-day adjusted weight (365DWT). Fixed effects of year of birth, season of birth, sex, birth type, and dam age on these traits were evaluated using linear procedures of SAS, 9.1. Similarly, BWT, 120DWT, 180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Hence, the selection on WT120 may significantly improve the post-weaning growth traits in Lohi sheep. Most of the earlier studies also found positive genetic and phenotypic correlations between growth traits in sheep [ 8 , 12 , 53 , 58 , 73 ].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Hence, the selection on WT120 may significantly improve the post-weaning growth traits in Lohi sheep. Most of the earlier studies also found positive genetic and phenotypic correlations between growth traits in sheep [ 8 , 12 , 53 , 58 , 73 ].…”
Section: Resultsmentioning
confidence: 93%
“…The growth of lamb is also influenced by the genotype of a dam for maternal impacts and her additive genes for growth [ 7 ]. Some other environmental factors which affect growth traits in sheep include season of birth (SOB), type of birth (TOB), year of birth (YOB), age of dam (AOD) and sex of animals [ 8 , 9 ]. It is well documented that the maternal effect is crucial in estimating the direct heritability of growth and reproductive performance traits [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%